A University and School Working in Partnership to Develop Professional Practice Knowledge for Teaching - Gravett, Sarah; Petersen, Nadine; Ramsaroop, Sarita (Frontiers in Education, 2019)
Abstract The article reports on the University of Johannesburg’s efforts at offering a practice-based teacher education program in partnership with a university-affiliated school (a ‘teaching school’) with a view to developing inquiry-oriented novice teachers. The research aimed at exploring what it takes to develop a ‘learningplace’ (Conway, Murphy and Rutherford 2014) conducive to student teachers’ development of professional practice knowledge and the role of mentoring in this regard. A two-phase process of generating data was used. In the first phase the published research on the university-affiliated school was analyzed, using qualitative content analysis to look for patterns across the historical unfolding of the findings of these papers. In phase two a questionnaire was administered involving final year student teachers in the teacher education program. The research shows that a teaching school, if integrated into the program design and delivery, provides a rich practice learning site for student teachers. In addition, mentoring in cognitive apprenticeship mode could indeed be a powerful contributor to student teachers’ professional development. However, the overall programme design is decisive. The preparation of teachers with strong professional practice knowledge requires attention to four interrelated aspects of program design, namely program identity, organizational structures, curriculum and teacher education pedagogy. Addressing these aspects in an integrated manner would be difficult without working closely with one or more partnership schools.